Exploring the Challenges of Teaching English via YouTube Live Streaming: A Qualitative Study - Adriyanti, Yulita; Sangkala, Ismail (Jurnal Edukasi Saintifik, 2025)
This study delves into the obstacles encountered by English teachers while utilizing YouTube Live Streaming as a platform for teaching. Focusing on educators from the SMP Unismuh Makassar YouTube channel engaged in live English instruction, the research aims to contribute to the understanding of YouTube Live Streaming as a teaching medium for English as a Foreign Language (EFL) learners. The study employs a qualitative approach, using purposive sampling to select two teachers as subjects. Data collection involves observing the difficulties faced by teachers during the live teaching and learning process. The study identifies four main categories of difficulties faced by teachers: communication barriers, time delays, lack of control, and self-confidence issues. The findings suggest that while YouTube can serve as a valuable source of teaching material, its limitations in fostering real-time interaction with students hinder its effectiveness as a primary teaching platform. The researcher concludes that platforms offering virtual face-to-face engagement may be more suitable for online teaching, reserving YouTube primarily as a supplementary learning resource rather than a live teaching tool. Particularly in contexts where face-to-face learning is feasible, leveraging alternative platforms for interactive engagement is recommended.